First general report - Shortt, Edward; Nethersole, Olga, 1870-1951 (London : People's League of Health)
1922-05 1922 1920s 55 pages : illustrations THE PEOPLE'S LEAGUE OF HEALTH. BALANCE SHEET, from 1st January to 31st December, 1921 LIABILITIES. £ s. d. £ s. d. CREDITORS— Rent 3 7 3 Badges 6 2 6 Lecturers 66 19 8 National Health Journal 11 0 0 Pamphlets 3 6 4 90 15 9 Sundry Creditors re Devonshire House Ball 1,138 1 2 1,228 16 11 GUARANTEE FUND SUBSCRIPTIONS 118 18 0 ENDOWMENT FUND SUBSCRIPTIONS 87 13 0 INCOME AND EXPENDITURE ACCOUNT— Balance 1st January, 1921, brought forward 158 11 10 Add Income in excess of Expenditure one year to date, per Income and Expenditure Account 1,278 15 10 1,437 7 8 (Signed) F. N. CURZON, Hon Treasurer. „ OLGA NETHERSOLE, Hon. Organiser. „ G. DAVID, Acting Secretary. £2,872 15 7 ASSETS. CASH AT BANKERS— £ s. d. £ s. d. London County, Westminster and Parr's Bank, Ltd., Hanover Square — Deposit Account 100 0 0 Special Deposit Account 100 0 0 Current Account — No. 3 2,507 9 1 2,707 9 1 Do. No. 1 Account Overdrawn £22 7 1 Do. No. 2 „ „ 20 6 8 42 13 9 2,664 15 4 CASH IN HAND 16 8 SUNDRY DEBTORS — Y.M.C.A. 6 6 0 L.C.C. 50 0 0 Devonshire House Balt 81 18 0 W.H. Smith & Son 12 7 11 150 11 11 STOCK — Badges 5 16 3 Pamphlets 25 15 5 31 11 8 TYPEWRITERS — Brought forward from last Balance Sheet 30 0 0 Depreciation written off 5 0 0 25 0 0 £2,872 15 7 REPORT OF THE AUDITORS.— We have examined the above Balance Sheet and the Income and Expenditure Account, with the books and vouchers, and have obtained all the information and explanations we have required. In our opinion the Balance Sheet is properly drawn up so as to exhibit a true and correct view of the state of the League's affairs according to the best of our information and the explanations given to us as shown by the Books. THAMES HOUSE, QUEEN STREET PLACE, E.C. 4. (Signed) EDWARD MOORE & SON, May, 1922 Chartered Accountants, Honorary Auditors. 200/B/3/2/C693/1/71